PR China as “the Responsible Great Power” – The Chinese Model of Foreign Investment and Assistance: The history of giving Chinese foreign investments and assistance - Arezina, Sanja (Napredak, 2021)
Shortly after its establishment, the People's Republic of China began to implement a policy of providing investments and assistance abroad. Although the motives for this were different in the decades that followed, the Chinese leadership never gave up on the decision to make foreign investment and assistance a central part of the Chinese foreign policy. To prove the basic hypothesis that the main reason for the development of the Chinese model of foreign investment and assistance is the intention of the Chinese leadership to show that the People's Republic of China is a "responsible great power" that contributes to solving important global problems, while working to achieve the most important goal – achieving "Chinese dream" by 2049, the author uses structural-functional analysis, comparative analysis, induction and deduction.